2018
DOI: 10.1063/1.5011761
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale identification of novel planar defect phases in heteroepitaxial YBa2Cu3O7−δ thin films

Abstract: We have discovered two novel types of planar defects that appear in heteroepitaxial YBa 2 Cu 3 O 7−δ (YBCO123) thin films, grown by pulsed-laser deposition (PLD) either with or without a La 2/3 Ca 1/3 MnO 3 (LCMO) overlayer, using the combination of high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) imaging and electron energy loss spectroscopy (EELS) mapping for unambiguous identification. These planar lattice defects are based on the intergrowth of either a BaO plane between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
3
2
0
Order By: Relevance
“…43 It is known that in the composite films, the concentration of these defects is usually much higher. 42,44,45 It is in agreement with our observation. The introduction of the LCMO layer in between YBCO layers could be a reason for the larger density of the intergrowths in the top YBCO layer.…”
Section: Resultssupporting
confidence: 92%
“…43 It is known that in the composite films, the concentration of these defects is usually much higher. 42,44,45 It is in agreement with our observation. The introduction of the LCMO layer in between YBCO layers could be a reason for the larger density of the intergrowths in the top YBCO layer.…”
Section: Resultssupporting
confidence: 92%
“…A layered crystal structure of YBa 2 Cu 3 O 7−δ films is clearly visualized together with an ∼10 nm-thick GDC/YSZ substrate in both samples (Figure 4a,c). Similar to previous observations of oxidized YBCO films, 20,21 many planar defects are also detected in the HAADF-STEM image of sample D. The crystal lattices of sample H (Figure 4b) and sample D (Figure 4d) agree well with the crystal structure models of YBa 2 Cu 3 O 6 and YBa 2 Cu 3 O 7 (Figure 1a). Thus, the similar crystal structures of YBa 2 Cu 3 O 6 and YBa 2 Cu 3 O 7 allow δ to be modulated by solid-state electrochemical redox treatments.…”
Section: ■ Experimental Sectionsupporting
confidence: 88%
“…We have reported earlier that the same metric, (Ba + Zr)/Cu, has a considerable effect on c-axis lattice mismatch between BZO and REBCO [48,61,63]. Multiple studies have reported presence of dense arrays of REBCO 124/248 type, 223 and other stacking faults [54,[83][84][85][86][87][88][89][90][91], and we have regularly observed the same features, as can also be seen in figure 2(d). One can readily envision a mismatch strain accommodation between c-axis of BZO and REBCO by inserting extra Cu-O planes to form 124-type defect at regular intervals in REBCO matrix to minimize mismatch between REBCO and BZO along the c-axis.…”
Section: In-plane Strain Accommodationsupporting
confidence: 84%